Motherhood in the American Woman Poet’s Perspective: A Short Glance at Allen’s Rock Me to Sleep - Nandy Intan Kurnia (Bina Nusantara University, 2015)
Article scrutinized one of the works of an American woman poet named Elizabeth Akers Allen. The poem under study entitled “Rock Me to Sleep”. It was a portrayal of motherhood. The speaker of this poem is a woman who is longing for the love of her mother. She is seeking for a way to ease her pain since she feels that she has lost her own battle of womanhood. Although the mother remains absent, the readers of the poem can sense the powerful love of the speaker of the poem toward her mother. Method of this study was library research that carried out by applying descriptive analytical methods. Data were collected from the primary and secondary sources. Results of this paper are the writer of poetry wants to warn people that womanhood in the patriarchal society can create many problems, and the only remedy for those problems is motherhood. Article also proves that a writer does not have to be a feminist to produce a literary text which discusses the issue of women, which has became the focus of feminism.